Book Thieves: Theft and Literary Culture in Nineteenth and Twentieth-Century Australia. (15th March 2017) - Piper, Alana
Abstract: Book thieves were a familiar figure to the reading public of Australia and other English-speaking nations during the late nineteenth and early twentieth century. Their exploits were covered in books about books, library and medical journals, and in newspapers that reported their appearances in court, and treated them as a humorous oddity in other coverage. This article examines the historic concerns and assumptions about book thieves, as well as what these tropes reveal about prevailing discourses regarding thieves more generally. The book thief – invariably constructed in the popular imagination as a middle-class male – was a classed and gendered figure, one at odds with contemporary understandings of theft as an act committed by members of an uncultured criminal class. By scrutinizing the development of popular conceptions of the book thief as an entity clearly distinguishable from the ordinary thief, I demonstrate the centrality of literacy and literary culture to how thieves themselves were read.